A utilização de mapas de tópicos na compatibilização de conteúdos hipertextuais semanticamente estruturados - Guilherme Baiao Salgado Silva (2008)
By taking into account characteristics of hypertext systems and problems of disorientation and cognitive overload common to these systems, this project has as its objective an analysis of hypertext documents which have undergone processes for construction of a conceptual framework, making use of faceted structures to represent content and improved information retrieval during navigation. The maingoal was to assess possible application of topic map technology during automation of the process aimed at compatibility of these structures. Two thesis papers were thus used as samples, from the Graduate Program in Information Sciences of the Federal University of Minas Gerais. These documents were already duly analyzed and structured in the prototype MHTX database. Faceted structures of these theses, which were previously represented in concept maps, were converted into topic maps.It was therefore possible to employ the merge property of topic maps to promote semantic links between the maps, and, consequently, among hypertext information resources. Results of the merge experiment were analyzed based on developed language compatibility theories belonging to Information and Library Sciences, starting in the 1960s. The main goals which were successfully met are as follows: (a) detailed concept of the topic map merging process, taking into consideration possiblecompatibility levels and applicability of this technology in integration of faceted structures; (b) a detailed sequence of steps to be followed in implementation of topic maps based on faceted structures.